2005
DOI: 10.1158/0008-5472.can-04-1740
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibits Novel Ginseng Metabolite-Mediated Apoptosis

Abstract: Recently, a novel intestinal bacterial metabolite of ginseng protopanaxadiol saponins, i.e., 20-O-(B-D-glucopyranosyl)-20(S)-protopanaxadiol (IH-901), has been reported to induce apoptosis in a variety of cancer cells. Here we show a differential effect of IH-901 on several cell types. Exposure to IH-901 for 48 hours at a supposedly subapoptotic concentration of 40 A Amol/L led to both apoptotic cell death and G 1 arrest in Hep3B cells, but only resulted in G 1 arrest in MDA-MB-231, Hs578T, and MKN28 cells. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 33 publications
6
43
1
Order By: Relevance
“…Along the same lines, Ming et al [55] suggested that IH-901 induced apoptotic cell death concurrently with cell cycle arrest in SMMC7721 cells. Similar effects of IH-901 in inhibiting the cell growth have been reported previously in other cancer cell lines [54].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Along the same lines, Ming et al [55] suggested that IH-901 induced apoptotic cell death concurrently with cell cycle arrest in SMMC7721 cells. Similar effects of IH-901 in inhibiting the cell growth have been reported previously in other cancer cell lines [54].…”
Section: Discussionsupporting
confidence: 87%
“…It is the integration of multiple survival and death signals that determine whether a cell survives or undergoes apoptosis. Moreover, IH-901 was shown to induce apoptosis in several different cancer cell lines [12,52], and several apoptosis-related molecules play important regulatory roles in IH-901-induced tumor cell death [53,54]. Along the same lines, Ming et al [55] suggested that IH-901 induced apoptotic cell death concurrently with cell cycle arrest in SMMC7721 cells.…”
Section: Discussionmentioning
confidence: 98%
“…165 There are a number of reports that cox-2 activity is associated with a suppression of spontaneous apoptosis in various types of cancer cells; conversely, cox-2 inhibitors have been reported to boost the responsiveness of certain cancer cell lines to cytotoxic drugs or radiotherapy. [166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184] (Some of these results need to be viewed circumspectly, however, as some cox-2-specific inhibitors such as celecoxib can exert proapoptotic effects that are independent of cox-2 inhibition. 185 ) Although the impact of cox-2 on apoptosis is likely mediated by PGE2 or other prostanoids, the mechanisms involved are less well understood than those that mediate the impact of NF-κB; increased expression of Bad and/or decreased expression of Bcl-2 appear to play a role in some cell lines.…”
Section: Multifocal Signal Modulation Therapies As Adjuvants To Cytotmentioning
confidence: 99%
“…Regarding liver cancer, Sho-Saiko-To (a mixture of seven herbs) was reported to inhibit proliferation of KIM-1 human hepatoma cells and KMC-1 cholangiocarcinoma cells (Yano et al 1994), and aqueous extracts of Paeoniae lactiXora and Bu-Zhong-Yi-Qi Tang (a mixture of ten herbs) have also been shown to suppress the growth of hepatoma cells (Kao et al 2001;Lee et al 2002). Recent studies revealed that the anticancer eYcacy of herbal agents has been linked to the modulation of apoptotic signaling, cell cycle regulation, angiogenic factors, matrix metalloproteinase (MMPs), invasion, and metastatic events in cancer cells Yim et al 2005;Lee et al 2006;Singh and Agarwal 2006), including liver cancer (Yuan et al 1998;Lee et al 2002;Yuan et al 2004).…”
Section: Introductionmentioning
confidence: 99%